Bacteria-Catalyzed Arginine Glycosylation in Pathogens and Host - Pan, Xing; Luo, Jie; Li, Shan (Frontiers in Cellular and Infection Microbiology, 2020)
In recent years, protein glycosylation in pathogenic bacteria has attracted more and more attention, and accumulating evidence indicated that this type of posttranslational modification is involved in many physiological processes. The NleB from several enteropathogenic bacteria species as well as SseK from Salmonella enterica are type III secretion system effectors, which have an atypical N-acetylglucosamine (N-GlcNAc) transferase activity that specifically modified a conserved arginine in TRADD, FADD, and RIPK1. NleB/SseKs GlcNAcylation of death domain proteins abrogates homotypic and heterotypic death receptors/adaptors interactions, thereby blocking an important antimicrobial host response. Interestingly, NleB/SseKs could also GlcNAcylate themselves, and self-GlcNAcylation of NleB, SseK1, and SseK3 are crucial for their biological activity during infection. In addition, EarP (EF-P specific arginine rhamnosyl transferase for Posttranslational activation) catalyzes arginine rhamnosylation of translation elongation factor P (EF-P). Importantly, this kind of N-linked protein glycosylation is not only important for EF-P dependent rescue of polyproline stalled ribosomes but also for pathogenicity in Pseudomonas aeruginosa and other clinically relevant bacteria. Glycosylation of arginine is unique because the guanidine group of arginine has a high acid dissociation constant value and representing an extremely poor nucleophile. Recently, the crystal structures of NleB, SseKs, EarP, arginine GlcNAcylated death domain-containing proteins, NleB/FADD-DD, and EarP/EF-P/dTDP-β-L-rhamnose were solved by our group and other groups, revealing the unique catalytic mechanisms. In this review, we provide detailed information about the currently known arginine glycosyltransferases and their potential catalytic mechanisms.